AN EVALUATION OF THE EXTENT SECONDARY SCHOOLS IN ZIMBABWE SENSITISE PUPILS ON SEXUAL AND REPRODUCTIVE HEALTH ISSUES. - Ruparanganda, Fenton (IJRDO- Journal of Educational Research, 2017)
This study sought to find out the extent to which the schools help in sensitizing secondaryschool pupils on sexual and reproductive health issues. The research was carried out inChimanimani district in Zimbabwe which is an agrobased area with severals farms .It ischaracterized by high prevalence of HIV/AIDS and other diseases of the reproductive system.A purposive sample of three schools was used; these were the only schools offering biologyand located in farming areas where the human population is vey high and is hard hit by HIV.A blend of qualitative and quantitative research methods was used. The data was collectedfrom biology teachers and biology students through questionnaires, interviews, and lessonobservation. The extent to which the school curriculum helps in raising pupils’ awarenesswas determined by examining the teachers’ knowledge, skills and attitudes towards sexualand reproductive health issues, analyzing the teaching methods, teaching aids, materialavailable and then pupils’ knowledge on sexual and reproductive health issues. Mostteachers in this research had little knowledge about sexual and reproductive health issues thatare not a result of an infection for example endometriosis, prostate carcinomas and fibroids.The biology syllabus does not address majority of the aspects it focuses on a narrow range ofissues. Students indicated that the curriculum helps them to understand other issues but itdoes not address real life skills required to manage certain issues like menstruation andstudents have pointed out that some of the knowledge about other sexual and reproductivehealth issues is from their peers.Teachers and parent do not discuss openly with secondaryschool students sexual and health issues.